FOREST CARBON SEQUESTRATION AND CLIMATE CHANGE MITIGATION - Jong Soo Ri; Ri Myong Hun; Pak Yong Hwa (Journal of Selvicoltura Asean, 2025)
Forest ecosystems play a critical role in mitigating climate change through carbon sequestration. Forests act as carbon sinks, absorbing large amounts of carbon dioxide (CO2) from the atmosphere and storing it in their biomass and soils. However, deforestation and forest degradation have significantly reduced the carbon storage capacity of forests, contributing to global warming. Given the urgency of climate change, understanding the potential of forest carbon sequestration is vital for informing climate mitigation strategies and policy. The purpose of this study is to evaluate the role of forests in carbon sequestration and their potential contribution to climate change mitigation. Specifically, the research aims to quantify carbon storage in different forest ecosystems and assess the effectiveness of forest conservation and reforestation efforts in enhancing carbon sequestration. A mixed-methods approach was employed, combining remote sensing data, field measurements, and carbon modeling techniques. Carbon stock estimates were obtained for tropical, temperate, and boreal forests across several regions. A comparison was made between intact forests, degraded forests, and reforestation sites. Data on tree biomass, soil carbon content, and forest management practices were collected over a two-year period. The results show that forests with higher biomass density and soil carbon content have significantly higher carbon sequestration rates. Tropical forests exhibited the highest carbon storage potential, followed by boreal forests. Reforestation efforts were found to enhance carbon sequestration, but the rate of carbon storage in reforested areas was slower compared to intact forests. This study highlights the critical role of forests in carbon sequestration and the importance of forest conservation and restoration for climate change mitigation. The findings support the need for global policies that prioritize forest preservation and reforestation as key strategies for reducing atmospheric CO2 levels.